The role of negative staff behavior and fairness on perceptions of post-release success among formerly incarcerated juveniles - Narvey, Chelsey S. (Journal of crime and justice, 2021)
A large body of literature has examined the impact of staff behavior in correctional settings on offenders’ likelihood of recidivism. However, gaps remain with respect to how staff behavior is related to other indicators of post-release success, including an individual’s perception of success upon release. In this study, we examine how correctional staff behavior is related to perceptions of success at staying out of trouble with the law and at succeeding in ordinary life goals among a sample of 679 serious juvenile offenders. Using data from Pathways to Desistance, our results show that while negative staff behavior was not significantly related to perceptions of success, fairness by staff was significantly related to individuals’ perceptions of success in both domains. Thus, those who perceived staff – and by extension the institution – as unfair were less likely to believe they would stay out of trouble with the law and succeed in life. These findings provide evidence that institutional climate is related to re-entry and policy efforts aimed at improving procedural fairness within correctional institutions are needed.